Assessing patient-reported peripheral neuropathy: the reliability and validity of the European Organization for Research and Treatment of Cancer QLQ-CIPN20 Questionnaire - Lavoie Smith, Ellen M. (Qual Life Res, 2013)
PURPOSE: This clinimetric analysis was conducted to evaluate the reliability, validity, and responsiveness to changeover time of the QLQ-CIPN20 when used to quantify patient-reported chemotherapy-induced peripheral neuropathy (CIPN). METHODS: Participants recruited to four cooperative group trials were pooled to create two groups (n = 376, 575): those who did versus did not receive neurotoxic chemotherapy. QLQ-CIPN20 internal consistency reliability was assessed using Cronbach's alpha coefficients. Instrument validity was assessed using factor analysis, by evaluating score correlations with other CIPN and pain measures, and by comparing scores between contrasting groups. Cohen's d was used to assess responsiveness to change. RESULTS: Alpha coefficients for the sensory, motor, and autonomic scales were 0.88, 0.88, and 0.78, respectively. However, autonomic scale and hearing loss items exhibited low item–item correlations (r ≤ 0.30) and thus were deleted. Moderate correlations were found between QLQ-CIPN20 and Brief Pain Inventory pain severity items (r 0.30–0.57, p ≤ .0001). Correlation between the QLQ-CIPN20 sensory and toxicity grading scale scores was low (r = .20; p ≤ .01). Mean scores were higher (worse) (p ≤ 0.0001) in individuals who did versus did not receive neurotoxic chemotherapy. The sensory and motor scales exhibited moderate-high responsiveness to change (Cohen's d = 0.82 and 0.48, respectively). Factor analysis indicated that the 16-item version formed distinct factors for lower and upper extremity CIPN, delineating typical distal to proximal CIPN progression. CONCLUSIONS: Results provide support for QLQ-CIPN20 sensory and motor scale reliability and validity. The more parsimonious and clinically relevant 16-item version merits further consideration.